Building a mathematical model for measuring and analyzing the general equilibrium in the Iraqi economy through the IS-lm-BP model - عباس, صلاح مهدي (Journal of Economics and Administrative Sciences, 2011)
In order to achieve overall balance in the economy to be achieved in different markets and at one time (market commodity, monetary and labor market and the balance of payments and public budget), did not provide yet a model from which to determine the overall balance in the economy and the difficulty of finding the inter-relationship between all these markets and put them applied in the form of allowing the identification of balance in all markets at once. One of the best models that have dealt with this subject is a model (LM-BP-IS), who teaches balance in the commodity market and money market and balance of payments and the importance of this issue This research tries to shed light on the reality of balance in the economy through this form for the period 1988 to 2008 and appeared Search Results the possibility of achieving a balance in the economy, but at low levels of output and high index of prices, interest rate, but the followers of policies proposed by the researcher can achieve balance in the economy at high levels of output and low interest rate and the index of prices.